2009
DOI: 10.1057/ajp.2008.38
|View full text |Cite|
|
Sign up to set email alerts
|

Identity Transformation in Medical Students

Abstract: This paper reviews the literature on the impact of medical school on personal development and consolidation of core identity. The limited literature relies on reports from medical students' journaling exercises, discussion groups, post-graduation surveys, and repeated personality testing. We review forces acting on medical students, with potential transforming effects. These forces include high external expectations and internal fear of superficial knowledge and skills, entry into the culture of medicine with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 30 publications
(31 reference statements)
0
46
0
Order By: Relevance
“…Strong, positive role models have been identified as key to the psychological well-being of medical students, and students must form relationships with them in order to succeed. 34 Role models are not just more senior doctors but might also be "students, residents, faculty members, nurses, and other team members". 34(p47) The changing world in which contemporary medical students live, learn, and will work has, however, raised some concerns about the continued efficacy of role-modelling as a pedagogical tool.…”
Section: (P49)mentioning
confidence: 99%
See 2 more Smart Citations
“…Strong, positive role models have been identified as key to the psychological well-being of medical students, and students must form relationships with them in order to succeed. 34 Role models are not just more senior doctors but might also be "students, residents, faculty members, nurses, and other team members". 34(p47) The changing world in which contemporary medical students live, learn, and will work has, however, raised some concerns about the continued efficacy of role-modelling as a pedagogical tool.…”
Section: (P49)mentioning
confidence: 99%
“…31,47 They can also suffer from low confidence about their abilities, a concern that may increase as others around them-for example patients and nurses-increasingly identify them as doctors. [33][34]48 Students who participated in one recent study reported that negative interactions with other professionals, particularly nurses, could leave them feeling stigmatised. 31 While fear of failure can be a source of stress for medical students, some work suggests that actual crises of identity, instances where a student's actions do not match who they are, can offer opportunities for positive professional identity by demonstrating both need and opportunity to change.…”
Section: (P766)mentioning
confidence: 99%
See 1 more Smart Citation
“…Strong mentoring has powerful effect on the level of empathy observed among medical students and may be an important protection against the development of cynicism. [12][13][14] The apprenticeship model also allows for negative acculturation through what is often referred to as the hidden curriculum. This pernicious dimension to medical training has been blamed for the persistence of undesirable behaviors among physicians, as well as for a collective de-professionalization perceived by some within and without medicine.…”
Section: Negative Role Modelingmentioning
confidence: 99%
“…A professional role consists of experiences based on working background, education, career [59], and personal experiences [5, 7]. At the same time, the construction of a personal self is closely related to one's history, family background, and life experiences, including the narrative organization of everyday life and specific events that are memorable to them [10, 11].…”
Section: Introductionmentioning
confidence: 99%